STUDY OF GROUND PORK THAWING DYNAMICS USING MAGNETIC RESONANCE IMAGING - Vladimir M. Stefanovskiy; Evgeny V. Morozov; Vyacheslav M. Bоuznik (Теория и практика переработки мяса, 2019)
Visualization of changes in shape and size of the frozen residue during the thawing of ground pork is implemented using magnetic resonance imaging. A technique has been developed to study the displacement of thawing front line without damage to integrity of the object being thawed. It has been established that the melting of bound water crystals outran the melting of free water crystals in meat. A mathematical model that adequately describes the experimental data obtained in the analysis of tomograms is proposed. Tomograms are an important information source for studying the patterns of heat and mass transfer during the thawing of frozen foods.